Patterns of cervical and masticatory impairment in subgroups of people with temporomandibular disorders–an explorative approach based on factor analysis - Ballenberger, N.; von Piekartz, H.; Danzeisen, M.; Hall, Toby (2018)
Objectives: To identify clinical patterns of impairment affecting the cervical spine and masticatory systems in different subcategories of temporomandibular disorder (TMD) by an explorative data-driven approach. Methods: For this observational study, 144 subjects were subdivided according to Research Diagnostic Criteria for TMDs into: Healthy controls, temporomandibular joint (TMJ) signs without symptoms, TMJ affected, temporomandibular muscles affected, or TMJ and muscles affected. Factor analysis and linear regression were applied to cervical spine and masticatory data to identify and characterize clinical patterns in subgroups. Results: Factor analysis identified five clinical dimensions, which explained 59% of all variance: Mechanosensitivity, cervical movement, cervical and masticatory dysfunction, jaw movement, and upper cervical movement. Regression analysis identified different clinical dimensions in each TMD subgroup. Conclusion: Distinct clinical patterns of cervical spine and masticatory function were found among subgroups of TMD, which has clinical implications for therapeutic management.